Internet-Based Materials in Enhancing College Students’ Writing Skill Viewed from Their Creativity - Fatimah Mulya Sari (TEKNOSASTIK, 2016)
This article mainly describes the effectiveness of internet-based materials and interaction effect between teaching materials and creativity in tecahing writing for college students. An experimental method was applied in this research. The population was the second semester of English Literature students consisting of 80 students: 40 students as the experimental group and 40 students as the control group. The research instruments used was writing test about an argumentative essay. A pre-test was given in the first meeting to know the validity and the reliability of the instrument. After giving treatments for three meeting, the writer conducted post-test to know the result. The finding of this research leads to the conclusion that the application of internet-based materials is more effective for teaching writing for the second semester of English Literature students. Besides, there is an interaction between tecahing materials and level of creativity. It is recommended that teachers might apply internet-based materials to teach writing for college students and teachers might give information about it to the students in order to enrich insight and get better learning to improve their writing skill. Therefore, it is important to provide high internet access or wi-fi in the class to increase the optimum writing achievement. By providing it, the students may find sample argumentative essays as many as possible to be read and to know the current issues being discussed.